Menimbang Urgensi Ukhuwah Wathaniyah dalam Kasus Intoleransi Beragama di Indonesia - Gusnanda Gusnanda; Nuraini Nuraini (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2020)
This paper discusses the phenomenon of religious intolerance in Indonesia. The spreading of various cases of intolerance lately is a big test for the integrity of Unity of the Indonesian Republic. One religion that is often cornered in the case of intolerance is Islam. Perhaps this is caused by many cases of radicalism, terrorism, and other social unrest carried out by Muslims. This assumption needs to be clarified because Islam never teaches its adherents to intolerance. Amid the undermining of this intolerant virus, love is needed in the motherland. In the Islamic paradigm, it is called Ukhuwah Wathaniyah or national brotherhood. This fraternity which was built with Ukhuwah Wathaniyah put the interests and love of the nation above all else. This conception of Ukhuwah Wathaniyah was practised by the Prophet Muhammad SAW. when he built a Medina society fourteen centuries ago. In the Indonesian Context, the concept of Ukhuwah Wathaniyah needs to beÂ re-actualized to realize religious tolerance in Indonesia.